2018
DOI: 10.1002/clc.23001
|View full text |Cite
|
Sign up to set email alerts
|

The role and outcome of cardiac rehabilitation program in patients with atrial fibrillation

Abstract: Background Atrial fibrillation (AF) is associated with diminished cardiac function, and exercise tolerance. Hypothesis We sought to investigate the role of cardiac rehabilitation program (CR) in patients with AF. Methods The study included 2165 consecutive patients that participated in our CR program between the years 2009 to 2015. All were evaluated by a standard exercise stress test (EST) at baseline, and upon completion of at least 3 months of training. Participants were dichotomized according to baseline f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…More research is needed to target interventions for high- patients, thereby addressing disparities. Targeted rehabilitation programs, including group education and physical training for patients with AF, significantly diminished the risk of mortality and cardiovascular hospitalizations [ 39 , 40 ]. These structured care programs have enhanced patient outcomes among patients with AF Reinforced, targeted, in-person education can improve quality of life, symptoms improvement, and medication adherence [41] .…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to target interventions for high- patients, thereby addressing disparities. Targeted rehabilitation programs, including group education and physical training for patients with AF, significantly diminished the risk of mortality and cardiovascular hospitalizations [ 39 , 40 ]. These structured care programs have enhanced patient outcomes among patients with AF Reinforced, targeted, in-person education can improve quality of life, symptoms improvement, and medication adherence [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared AF patients and non-AF patients who joined a cardiac rehabilitation programme for other cardiovascular diseases or cardiovascular risk factors. Younis et al found that patients with AF initially had lower physical capacity than non-AF participants, but improvement in physical capacity diminished the risk of total mortality and cardiovascular hospitalization for both groups (27). In a case control study Reed et al found that rehabilitation improved QoL in both groups, but to a greater extent in patients without AF (28).…”
Section: Discussionmentioning
confidence: 99%
“…В исследовании Osbak PS, et al (2012) у больных (n=49) с ФП после 12-мес. курса ФТ (на велотренажере с интенсивностью 70% от максимальной мощности в течение 30 мин, в виде степ-нагрузки и бега с напряжением 14-16 баллов по шкале Борга) мощность нагрузки при ВЭМ-пробе возрастала на 8,8% (р<0,001) и ЧСС в покое уменьшилась на 9,1% (р=0,049) [13] [15]. С ростом параметров ФРС связывают и лучший контроль основных факторов риска у пациентов с ФП при разной стратегии контроля ритма сердца в реабилитационных программах [16].…”
Section: результатыunclassified